(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article describes the problems of market of Renewable sources Energy and possibility of his development in the closest summers. To favour this legal settlement should stable how and profitable economic reports for manufacturers. They are the important element of created market green and red certificates, which across Freight Energetistic Exchange become with element of financial turn. On development of created market the biopaliw calculate first of all the farmers which would can use their productive supplies and to enlarge across market of biomass the earnings.